SEBORRHEIC DERMATITIS TREATMENT WITH MUSTARD OIL: A CASE REPORT (International Journal of Ayurveda and Pharma Research, 2021)
Seborrheic dermatitis is a chronic skin disease which is primarily associated with sp. Malassezia infection on the epidermis of the skin. The disease is characterized by massive skin exfoliation of seborrheic regions like forehead, behind pinna of ear, armpits, nasolabial fold, dandruff in the scalp, etc. Around 5% of general population is a victim of this disease.  The patient condition often becomes a hindrance for his or her livelihood and results into low self-esteem. Modern medical therapy recommends use of selenium sulfide sulfide, azole group of antibiotics like ketokonazole, Econazole, Clotrimazole, etc. In severe cases corticosteroids like Betamethasone dipropionate (0.05% potency) is also used. But all these have not given clinically efficient results. The clinical symptoms visible in this disease are scaling or exfoliation of skin; redness and swelling of affected regions along with itching. Neutrophilic infiltration in the epidermal crust and dense presence of inflammatory mediators in the region are found in the region on performing histological studies using skin biopsy.In the ancient Indian medical system of Ayurveda, mustard oil or Sarshapa taila has been characterized as deep penetrating, hot potency, pungent smelling fluid effective against skin itching and urticaria. This is a case report of experimental mustard oil therapy on a patient with Seborrheic dermatitis. It is being addressed to the global health community from both the fields of modern medicine and Ayurveda to carry a much deeper study on the topic and the therapy method which is being shown in this research.